Strategi Komunikasi Interpersonal Guru Ngaji dalam Menyampaikan Nilai-Nilai Keislaman kepada Santri di TPQ Margoyoso Masjid Blangkon - Rizky Rahmawati; Ahmad Rifa'i (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses the interpersonal communication strategies used by religious teachers in conveying Islamic values ​​to students at TPQ Margoyoso Blangkon Mosque. The background of this study is based on the importance of the role of religious teachers as agents of change in shaping the character of students through an effective communication approach. The purpose of this study is to describe the interpersonal communication strategies applied and their influence on students' understanding of Islamic values. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study indicate that religious teachers apply communication strategies such as a personal approach, two-way dialogue, empathy, and role modeling. This strategy has proven effective in building emotional closeness and increasing students' understanding and practice of Islamic values. The implications of this finding indicate that the success of conveying Islamic values ​​does not only depend on the teaching materials, but also on the quality of interpersonal communication between teachers and students. Therefore, religious teachers need to continue to hone their communication skills to create an inspiring learning environment that touches the affective aspects of students.